A Reevaluation of the Status of the Foxsnakes Pantherophis gloydi Conant and P. vulpinus Baird and Girard (Lepidosauria). (18th May 2011) - Crother, Brian I.; White, Mary E.; Savage, Jay M.; Eckstut, Mallory E.; Graham, Matthew R.; Gardner, David W.
Abstract : As currently understood, there are two species of foxsnakes (Eastern Foxsnake, Pantherophis gloydi Conant and Western Foxsnake, P. vulpinus Baird and Girard) that are separated by a large geographic disjunction that encompasses almost all of Michigan, eastern Indiana, and eastern Ohio. Phylogenetic analysis of mtDNA data of individuals from throughout the ranges of the two species inferred reciprocally monophyletic clades that revealed a new species boundary, the Mississippi River. The single key morphological character also shows a major difference at the river. Because the localities of the holotypes of P. gloydi and P. vulpinus are both within the new range of the eastern form, gloydi is recognized as a junior synonym of vulpinus and a new name, P. ramspotti, is erected for the western form. The estimates of divergence time and historical biogeography suggest that Pleistocene glaciation and the Mississippi River played a key role in speciation.